Do Dietary Supplements Affect Inflammation, Oxidative Stress, and Antioxidant Status in Adults with Hypothyroidism or Hashimoto's Disease?-A Systematic Review of Controlled Trials - Katarzyna Kubiak; Maria Karolina Szmidt; Joanna Kaluza; Agnieszka Zylka; Ewa Sicinska (MDPI AG, 2023)
This systematic review aims to summarise the results of controlled trials on dietary supplements (DS) usage and inflammation, oxidative stress, antioxidant status, and thyroid parameter improvement in hypothyroidism (HT)/Hashimoto's thyroiditis (AIT) patients. The study protocol was registered with PROSPERO (no. CRD42022365149). A comprehensive search of the PubMed, Scopus, and Web of Science databases resulted in the identification of nineteen randomised controlled trials and three non-randomised studies for the review; three studies examined the effect of supplementation with vitamin D, twelve studies-with selenium, and seven studies-with other DS. Based on very limited evidence, the lack of influence of vitamin D supplementation on inflammatory parameters was found, while no studies have examined oxidative stress and antioxidant status parameters, and only one provided results for a single thyroid parameter after an intervention. Some evidence was found proving that selenium supplementation may decrease inflammation and improve thyroid parameters, but reaching a conclusion about its influence on oxidative stress and antioxidant status is not possible because of the insufficient number of studies. Additionally, due to examining other DS (e.g., multicomponent, Nigella sativa, and genistein) only in single studies, conclusions cannot be drawn. Further long-term, high-quality randomised controlled trials are necessary to better understand the influence of DS on inflammation, oxidative stress, and antioxidant status, as well as their potential to improve thyroid gland function in HT/AIT patients.